Cortical Glutamate/GABA Imbalance after Combined Radiation Exposure: Relevance to Human Deep-Space Missions. (15th September 2019) - Kokhan, Viktor S.; Anokhin, Petr K.; Belov, Oleg V.; Gulyaev, Mikhail V.
Abstract: Ionizing radiation (IR) is one of the major biological limiting factors of human deep-space missions. Despite the dominant paradigm about the negative effects of IR on the CNS, the anxiolytic, antidepressant, anti-aggressive, and pro-cognitive effects have recently been discovered. The mechanisms of these phenomena remain undisclosed. Here, we study the effects of combined IR exposure (γ-rays and 12 C nuclei) on the psycho-emotional state, cognitive abilities, and the metabolism of glutamate and GABA in Wistar rats, with an emphasis on the age factor. Irradiation resulted in the anxiogenic effect, reversing during maturation, and the sustained increase in spatial learning performance. A persistent decrease in the content of GABA was observed, which confirmed the hypothesis of disinhibition of the CNS under irradiation with moderate doses, proposed earlier. Glutamate/GABA imbalance was accompanied by an increase in the metabolism of these neurotransmitters: an increase in expression level of GLT-1, GAD65, GABAT and GAT1. Besides, a decrease in the expression level of NR1 subunit of the NMDA receptor was noted. Notably, the maturation of rats led not only to the rebalancing of the glutamate/GABA ratio by reducing the glutamate content, but also to leveling the differences in the expression levels of the analyzing biomolecules. Thus, the combined action of IR at moderate doses resulted in long-term changes in psycho-emotional status and, surprisingly, an increase in the efficiency of spatial learning performance. We suggest that IR (within the range of composition and doses used) can be relatively safe for the functions of the CNS. Highlights: Ionizing radiation stimulates spatial learning performance. Reduced GABA-ergic control in the cortex leads to disinhibition of the CNS. Upregulation of GABA transaminase expression caused decrease in total GABA content. Glutamate/GABA ratio rebalancing is the evidences of an extensive repair process.